2007
DOI: 10.1063/1.2715513
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric characteristics of BiFeO3 thin films prepared via a simple chemical solution deposition

Abstract: BiFeO 3 ͑BFO͒ thin films were fabricated on Pt͑111͒ / Ti/ SiO 2 / Si substrates by using a polymeric precursor solution under appropriate crystallization conditions. The capacitance dependence on voltage is strongly nonlinear, confirming the ferroelectric properties of the films resulting from the domain switching. The leakage current density increases with annealing temperature. The polarization electric field curves could be obtained in BFO films annealed at 500°C, free of secondary phases. X-ray photoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 15 publications
(12 reference statements)
1
18
1
Order By: Relevance
“…And with the lamination temperature increasing, the bulk density reaches the maximum value of 7.87 g/cm 3 at 110 o C. Besides the temperature, the pressure also shows a great effect on the bulk density. It can be observed that the bulk density first slightly increased with the pressure rising from 40 MPa to 120 MPa, then decreased rapidly to about 6.66 g/cm 3 when the pressure further increased to 160 MPa. These results above indicate the densest ceramics are able to obtain at the lamination temperature of 110 o C with the pressure of 40 MPa.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…And with the lamination temperature increasing, the bulk density reaches the maximum value of 7.87 g/cm 3 at 110 o C. Besides the temperature, the pressure also shows a great effect on the bulk density. It can be observed that the bulk density first slightly increased with the pressure rising from 40 MPa to 120 MPa, then decreased rapidly to about 6.66 g/cm 3 when the pressure further increased to 160 MPa. These results above indicate the densest ceramics are able to obtain at the lamination temperature of 110 o C with the pressure of 40 MPa.…”
Section: Resultsmentioning
confidence: 91%
“…It is noted that the bulk density of the ceramics laminated at 20 o C with 40 MPa is only 6.99 g/cm 3 . And with the lamination temperature increasing, the bulk density reaches the maximum value of 7.87 g/cm 3 at 110 o C. Besides the temperature, the pressure also shows a great effect on the bulk density.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations